Functionalized Palladium Nanoparticles for Hydrogen Peroxide Biosensor - H. Baccar; T. Ktari; A. Abdelghani (International Journal of Electrochemistry)
We present a comparison between two biosensors for hydrogen peroxide (H2O2) detection. The first biosensor was developed by the immobilization of Horseradish Peroxidase (HRP) enzyme on thiol-modified gold electrode. The second biosensor was developed by the immobilization of cysteamine functionalizing palladium nanoparticles on modified gold surface. The amino groups can be activated with glutaraldehyde for horseradish peroxidase immobilization. The detection of hydrogen peroxide was successfully observed in PBS for both biosensors using the cyclic voltammetry and the chronoamperometry techniques. The results show that the limit detection depends on the large surface-to-volume ratio attained with palladium nanoparticles. The second biosensor presents a better detection limit of 7.5 μM in comparison with the first one which is equal to 75 μM.